2021
DOI: 10.3897/jhr.87.75363
|View full text |Cite
|
Sign up to set email alerts
|

 Gryon aetherium Talamas (Hymenoptera, Scelionidae): Parasitoid of Bagrada hilaris (Burmeister) (Hemiptera, Pentatomidae) Adventive in Chile

Abstract: A parasitoid wasp, Gryon aetherium Talamas (Hymenoptera, Scelionidae), was reared from eggs of the invasive stink bug Bagrada hilaris (Burmeister) (Hemiptera, Pentatomidae) in Chile. The identification of G. aetherium, which is under study as a biological control agent, was made with morphological and molecular data in the context of a recent taxonomic treatment of this species. The presence of an adventive population of G. aetherium in South America has implications for biological control of B. hilaris in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Gryon aetherium was present at all but 1 of the sampled sites in this study and may now be widely distributed throughout California and western North America more broadly. In Mexico, G. aetherium (reported as G. myrmecophilum ) emerged from sentinel B. hilaris eggs (Felipe-Victoriano et al 2019), and has also been reported in Chile (Rojas-Gálvez et al 2021). It likely is adventive in the New World because no records exist of it before the arrival of B. hilaris (Talamas et al 2021).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gryon aetherium was present at all but 1 of the sampled sites in this study and may now be widely distributed throughout California and western North America more broadly. In Mexico, G. aetherium (reported as G. myrmecophilum ) emerged from sentinel B. hilaris eggs (Felipe-Victoriano et al 2019), and has also been reported in Chile (Rojas-Gálvez et al 2021). It likely is adventive in the New World because no records exist of it before the arrival of B. hilaris (Talamas et al 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Gryon aetherium and T. hyalinipennis have since appeared in the invasive range of B. hilaris in the New World, where they are likely to be adventive. Gryon aetherium was found attacking B. hilaris eggs in California (Hogg et al 2021, 2022), Mexico (Felipe-Victoriano et al 2019, reported as G. myrmecophilum ) and Chile (Rojas-Gálvez et al 2021), and T. hypalinpennis emerged from sentinel B. hilaris eggs in southern California (Ganjisaffar et al 2018). Previous studies in California documented the presence of G. aetherium at individual sites, either using previously frozen sentinel eggs (Hogg et al 2022) or a combination of sentinel and naturally laid eggs (Hogg et al 2021), but the distribution and impact of G. aetherium in California remain unclear.…”
Section: Introductionmentioning
confidence: 99%